Humus stock degradation and its impact on phosphorus forms in arable soils – a case of the Ukrainian Forest-Steppe Zone. Issue 1 (1st January 2018) - Spychalski, Waldemar; Grzebisz, Witold; Diatta, Jean; Kostarev, Dima
Abstract: Soil humus degradation strengthens nutrient mining, especially phosphorus. This study was carried out on the Ukrainian Forest-Steppe Zone (UFSZ). A total of 21 soil profiles have been investigated: 11 Phaeozems, 6 Luvisols, and 4 Chernozems. Soils were tested for particle size distribution, calcium carbonate (CC), pH, and organic carbon (Corg ). The evaluation of humus degradation as a reason of P depletion was performed based on indicators such as Humus Stock Gap (HSG), Humus Stability Index (S), and Yield Gap/Gain (YG/G). In order to evaluate the degree of P depletion, total phosphorus (Ptot ) and its five fractions: water soluble – PH2O, exchangeable – PEX, bound to Fe and Al – PFe/Al, bound to Ca – PCa, and residual P – Pres, have been determined. Data revealed that in 14 of 21 investigated soils, S indices were below the threshold its value of nine, considered as the balanced content of humus with respect to soil texture. Next, in 11 of 21 cases, the negative humus balance indicates the yield gap in Phaeozems and Chernozems. The first three P pools (PH2O, PEX and PAl/Fe ) in Phaeozems were exhausted, constituting less than 10% of the Ptot . In Phaeozems, PAl/Fe, in Luvisols, PEX, and in Chernozems, PH2O fractions were basic indicators of available P status. Their pools were directly or indirectly controlled by PCa. Humus content in Phaeozems and Chernozems revealed as the key factor impacting both total P and/or its available resources. Amelioration of P depletion requires efforts oriented on restoration of soil humus stock, concomitant with P fertilization.